Preliminary Concepts of Dynamical Systems - Mukherjee, Nayana; Poria, Swarup (International Journal of Applied Mathematical Research, 2012)
Dynamical system is a young and vigorously growing area of research which promises enormous potential and opportunities. This paper aims to  introduce some of the  preliminary concepts of dynamical systems.   Many application sides of the subject are noted to encourage the reader for future developments. Resources are supplied in the references for   further reading.